Efficacy of a Ceftazidime-Avibactam Combination in a Murine Model of Septicemia Caused by Enterobacteriaceae Species Producing AmpC or Extended-Spectrum β-Lactamases - Levasseur, Premavathy (Antimicrob Agents Chemother, 2014)
Avibactam is a novel non-β-lactam β-lactamase inhibitor that has been shown in vitro to inhibit class A, class C, and some class D β-lactamases. It is currently in phase 3 of clinical development in combination with ceftazidime. In this study, the efficacy of ceftazidime-avibactam was evaluated in a murine septicemia model against five ceftazidime-susceptible (MICs of 0.06 to 0.25 μg/ml) and 15 ceftazidime-resistant (MICs of 64 to >128 μg/ml) species of Enterobacteriaceae, bearing either TEM, SHV, CTX-M extended-spectrum, or AmpC β-lactamases. In the first part of the study, ceftazidime-avibactam was administered at ratios of 4:1 and 8:1 (wt/wt) to evaluate the optimal ratio for efficacy. Against ceftazidime-susceptible isolates of Klebsiella pneumoniae and Escherichia coli, ceftazidime and ceftazidime-avibactam demonstrated similar efficacies (50% effective doses [ED(50)] of <1.5 to 9 mg/kg of body weight), whereas against ceftazidime-resistant β-lactamase-producing strains (ceftazidime ED(50) of >90 mg/kg), the addition of avibactam restored efficacy to ceftazidime (ED(50) dropped to <5 to 65 mg/kg). In a subsequent study, eight isolates (two AmpC and six CTX-M producers) were studied in the septicemia model. Ceftazidime-avibactam was administered at a 4:1 (wt/wt) ratio, and the efficacy was compared to that of the 4:1 (wt/wt) ratio of either piperacillin-tazobactam or cefotaxime-avibactam. Against the eight isolates, ceftazidime-avibactam was the more effective combination, with ED(50) values ranging from 2 to 27 mg/kg compared to >90 mg/kg and 14 to >90 mg/kg for piperacillin-tazobactam and cefotaxime-avibactam, respectively. This study demonstrates that the potent in vitro activity observed with the ceftazidime-avibactam combination against ceftazidime-resistant Enterobacteriaceae species bearing class A and class C β-lactamases translated into good efficacy in the mouse septicemia model.